ANALISIS NILAI TUKAR NELAYAN (NTN) BERDASARKAN ALAT TANGKAP DI PPI SAWANG BAU KABUPATEN ACEH SELATAN - Syarifah Zuraidah; Zuriat Zuriat; Teuku Amarullah; Uswatuh Hasanah; Esi Lianda (JURNAL PERIKANAN TROPIS, 2022)
Abstract The welfare system plays a significant role in communal life. The source of welfare is seen from an economic perspective. The size of a person's opinion describes what his job is. In terms of the economy, fishermen have long been perceived as being in poverty. At PPI Sawang Ba'u, fishermen use purse seines, fishing lines, and nets as their primary means of capture. In order to meet household demands and achieve success, income and expenses must be matched. The study's objective was to estimate the exchange rate for fishing gear among the fishermen in PPI Sawang Ba'u in the South Aceh District. A quantitative descriptive methodology was used in this study. The sample consisted of 83 crew members (ABK), including 70 responses for purse seines, 7 for fishing rods, and 6 for net fishing gear. The highest average monthly income from purse seine fishing is RP 4,021,000, and the lowest average monthly income from net fishing is RP 1,798,333. The greatest average monthly expenditure from net fishing is RP 2,845,367, and the lowest average monthly expenditure from purse seine fishing is RP 2,168,599, respectively. When the Fishermen's Exchange Rate (NTN) at PPI Sawang Ba'u is greater than 1, it indicates that the fishermen are prosperous. Conversely, when the NTN is lower than 1, it indicates that the fishermen are not prosperous, and when it is lower yet when employing fishing nets, it indicates that the fisherman are not successful.Keywords: expenditure, fishermen exchange rate, fishing gear, income, welfare